2018
DOI: 10.1002/pros.23655
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone‐releasing hormone antagonists reduce prostatic enlargement and inflammation in carrageenan‐induced chronic prostatitis

Abstract: The study demonstrates that GHRH antagonists could be beneficial for the treatment of prostatic inflammation and BPH in part by inhibiting the growth-promoting and inflammatory effects of locally produced GHRH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 54 publications
5
23
1
Order By: Relevance
“…We finally evaluated the effects of MIA-690 ( www.nature.com/scientificreports www.nature.com/scientificreports/ Discussion GHRH and mRNAs for GHRH-R have been found in rat cortex and brain stem 22,23 , and various reports suggested that GHRH might play a key role in cognitive and mood disorders 20,[24][25][26][27][28] . GHRH-antagonists compounds can exert powerful antitumor effects, possibly related in part to their antinflammatory and antioxidant properties 17,[29][30][31][32][33] . In the present study we show that MIA-690, a GHRH antagonist, and MR-409, a GHRH analog, exhibit antinflammatory and antioxidant effects on prefrontal cortex specimens, ex vivo (Figs.…”
Section: Mr-409 Induced Down Regulation Of P Ghrh-r Gene and Protein mentioning
confidence: 99%
See 1 more Smart Citation
“…We finally evaluated the effects of MIA-690 ( www.nature.com/scientificreports www.nature.com/scientificreports/ Discussion GHRH and mRNAs for GHRH-R have been found in rat cortex and brain stem 22,23 , and various reports suggested that GHRH might play a key role in cognitive and mood disorders 20,[24][25][26][27][28] . GHRH-antagonists compounds can exert powerful antitumor effects, possibly related in part to their antinflammatory and antioxidant properties 17,[29][30][31][32][33] . In the present study we show that MIA-690, a GHRH antagonist, and MR-409, a GHRH analog, exhibit antinflammatory and antioxidant effects on prefrontal cortex specimens, ex vivo (Figs.…”
Section: Mr-409 Induced Down Regulation Of P Ghrh-r Gene and Protein mentioning
confidence: 99%
“…Accordingly, various studies showed that GHRH and GHRH antagonists can influence the inflammatory and reduction/oxidation (redox) status in cancer and other tissues 29,33 . www.nature.com/scientificreports www.nature.com/scientificreports/ In particular, MIA 690 decreased inflammation by reducing the infiltration of macrophages and leucocytes, the production of TNF-α, IL-1β, and monocyte chemotactic protein-1 (MCP-1) in tissue after insult with lipopolisaccaride (LPS) and the production of the pro-inflammatory markers in carrageenan-induced chronic prostatis 31,32 . In addition, MIA-690 showed antioxidant and neuroprotective properties 28 .…”
Section: Mr-409 Induced Down Regulation Of P Ghrh-r Gene and Protein mentioning
confidence: 99%
“…In other studies, GHRH stimulated multiple pathways involved in inflammation and growth in both BPH-1 and PrEp cells including NFκB p65, AKT, ERK1/2, EGFR, and STAT3. 24 The current study investigated the effects of GHRH antagonist MIA 602, GHRH and GHRH agonist MR 409 in the regulation of inflammatory processes; which strongly affect the endothelial permeability of BPAECs. We decided to focus on the effects of those compounds toward the expression of P53, since P53 has been recently shown to be a major regulator of the endothelium permeability.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that carrageenan induces chronic prostatic inflammation in rats and increases mRNA expression of Spp1, which encodes osteopontin (OPN) 16 . OPN is a secreted phosphoglycoprotein and an extracellular matrix constituent 17 .…”
Section: Introductionmentioning
confidence: 99%